Identifikasi Bahaya Dan Manajemen Resiko Sebagai Implementasi Safety Management System Di Bandar Udara Domine Eduard Osok - Muliasari, Ataline (Sekretariat Badan Penelitian dan Pengembangan Perhubungan, 2010)
Airport securitt; is a process of realization of airport security. Related to the abave, the security of anairport will go to support the realization of flight safety. Domine &iuard Osok Airport are still tryingto realize the security of airports with strict monitoring of passenger luggage. However, it is lesssupported btj the quality and quantity of equipment and human resourres. For example, the absenreof X-RJJy facilities fur VIP lounge. So it am re possible dangerous goods included in the aircraft cabinthrough the door.Based on analysis of hazard identification and safett; risk management, it appears that DomineE.duard Osok Airport still has a ven; high level of risk to flight safety.Keywords: Safety Management Systems, Risk